2018
DOI: 10.1080/02680939.2018.1458995
|View full text |Cite
|
Sign up to set email alerts
|

Teacher or friend? – consumer narratives on private supplementary tutoring in Sweden as policy enactment

Abstract: Private supplementary tutoring (PST) is a worldwide enterprise that comes in a variety of forms and with a growing number of students. Sweden, together with the other Nordic countries, has a relatively short history of large-scale organised supplementary education, which can be explained by its confidence in regular mainstream education. In recent years though, this picture has partly changed, and today families in Sweden are offered different kinds of education services outside the ordinary school system. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 33 publications
2
39
0
1
Order By: Relevance
“…Unlike school teachers, private tutors who interact with pupils on a more individual and personal basis seem to provide the care and support that pupils need while being exposed to pressure for high academic achievements. The present study, which is based on a quantitative analysis, corroborates with a recently found narrative in Swedish education, presented by Hallsén and Karlsson (), who elucidate that PT contributes to the individual pupil by providing encouragement and motivation on a more personal level compared to that expected from school teachers. This seems also to hold true for the Israeli education system, where the average class size is high (28 versus 23 in the OECD), limiting teachers’ ability to provide more personal and individual consideration to each pupil.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unlike school teachers, private tutors who interact with pupils on a more individual and personal basis seem to provide the care and support that pupils need while being exposed to pressure for high academic achievements. The present study, which is based on a quantitative analysis, corroborates with a recently found narrative in Swedish education, presented by Hallsén and Karlsson (), who elucidate that PT contributes to the individual pupil by providing encouragement and motivation on a more personal level compared to that expected from school teachers. This seems also to hold true for the Israeli education system, where the average class size is high (28 versus 23 in the OECD), limiting teachers’ ability to provide more personal and individual consideration to each pupil.…”
Section: Discussionsupporting
confidence: 91%
“…However, there is no clear examination of the link between pupils’ views and experiences of private tutors on their attitudes towards school teachers. Learning about the possible effect of PT on school teachers can be drawn from Hallsén and Karlsson's () study in Sweden, which was based on qualitative data analysis of stories published on a website of a private supplementary tutoring company. They concluded that ‘The private tutor appears … as a solution to problems that are beyond both parents and school, and thus as indispensable … The marketing of private tutoring can … work to delegitimize formal education … and encourage parents to take the expected responsibility for the education of their children by looking for help outside of the formal education system’ (p. 12).…”
Section: Pupils’ Pt Experience and Perception Of School Teachersmentioning
confidence: 99%
“…Up until now, comparative studies on tutors have gathered and analysed quantitative data on tutor characteristics in terms of education, employment, main profession, and age. There is, however, a growing number of qualitative studies looking more closely at tutor identities and roles in different ST contexts (Barkhuizen 2017;Davis 2013;Hallsén and Karlsson 2019;Kozar 2013;Popa and Acedo 2006;Trent 2016;Yung and Yuan 2020). These studies focus, as qualitative research tends to do, on local manifestations of ST.…”
Section: Research On Private Tutorsmentioning
confidence: 99%
“…The role of high-stakes exams in the formal educational system is relevant to tutor identities, as shown by Yung and Yuan (2020) study of tutor biographies posted online in Hong Kong, in which a discourse analysis illustrates how an entertainment business discourse was used to promote the hybrid tutor identity of the 'exam expert-star teacher ' (p. 11). Formal education may be relevant to online marketing in other ways as well, as shown in a study of online ST marketing by Hallsén and Karlsson (2019). Through a positioning analysis of three consumer narratives used for marketing purposes on the website of a Swedish ST company, they illustrated how the tutor identities of stand-in teacher, older sibling, and parental control instrument were constructed in relation to a discourse on parental responsibility for children's academic achievements.…”
Section: Research On Private Tutorsmentioning
confidence: 99%
See 1 more Smart Citation